Multiple Measures for the Prediction of Counsellor Trainee Effectiveness - Ridgway, Ian R.; Sharpley, Christopher (Canadian Journal of Counselling and Psychotherapy, 2011)
A set of five variables was used to predict the counselling effectiveness of 42 counsellor trainees who received microskills-based instruction. Assessment and analysis of posttraining performance data, which used a different set of three outcome measures, revealed a significant relationship between the set of predictor variables and the set of outcome measures of counselling effectiveness. High affective empathy and low purposein- life in the predictor set were found to predict counselling skills in the outcome set. Implications for training are discussed.